DEVELOPMENT OF INTERACTIVE MULTIMEDIA TOWARDS ECONOMIC PROBLEMS ON ECONOMIC SUBJECTS FOR SOCIAL SCIENCE CLASS X STUDENTS AT DARMA YUDHA HIGH SCHOOL - Simanjuntak, SahalaFreddy; Suarman; Indrawati, Henny (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2019)
This research aims to produce interactive multimedia using Lectora inspire in learning economic using the 4D development model. This work employed a qualitative descriptive method. Interactive multimedia was produced through three stages: definition, design, and development. This research was limited to the development stage. Definition stage comprised the preliminary analysis, curriculum analysis, material analysis, characteristic analysis, and formulation. Meanwhile, the design stage included pre-production from flowchart and storyboard making, media production to final activities: mixing, editing, and finalization. The development stage encompassed the following: (1) Expert appraisal, which was expert validation and revision with a result of very appropriate based on validation of media expert, material expert and language expert, and (2) Developmental testing, consisting of a small-scale tryout with a score of 81.98% (very appropriate). Our proposed system was very appropriate, according to the result of validation by an expert in a small scale try-out; thus it can be used in economic learning at SMA Darma Yudha.